SOFTWARE FOR VALUE MONITORING AS AN ADAPTATION TOOL FOR CHANGES IN PROJECT STEAKHOLDERS’ REQUIREMENTS - Husieva, Yu. Yu.; Chumachenko, I. V. (Radio Electronics, Computer Science, Control, 2019)
Context. In a dynamic environment where stakeholder requirements may change, traditional project monitoring and control methods have some limitations. Therefore, there is a need to develop approaches and appropriate software to monitor the requirements of the software project stakeholders, in particular, taking into account their personal assessment of the value of requirements and resources. Objective. The goal of the work is the development of a method for monitoring the value of the software project stakeholders’ requirements and the corresponding tools for its implementation. Method. Methods of analysis and synthesis, operations on matrices, a system of weighting coefficients of Fishburne, methods of the project management theory are used. A value-based approach to monitoring the requirements of the project stakeholders is proposed. The approaches to determining the value of the requirements of stakeholders are proposed based on available information from standard project documents. The method of project stakeholders’ value monitoring, in particular, for software projects, and the appropriate tools for its implementation are proposed. Results. Based on the value-added approach to monitoring requirements, tools have been developed to track the achievement of the project’s planned value. Compliance of the proposed method with the processes of traditional project management allows using standard software for generating initial data and displaying the results of calculations. Conclusions. Based on the method of the earned requirements of the project, a method of requirements’ value monitoring has been developed that, unlike existing ones, will allow to take into account personal assessments of the value of requirements and resources during project monitoring; to carry out relevant forecasts and develop strategies for working with certain interested parties or groups. The tools of using the proposed method in the MS Project environment provide information support for making fundamental decisions on adapting the project to changes in the requirements of stakeholders, in particular, the schedule variance and schedule performance index is calculated. The prospect of further research is to solve the problem of optimizing the distribution of resources in the project in the conditions of maximizing the achieved value of the project.